2012
DOI: 10.1021/ja210388g
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Cyclizations of Silyloxyenynes Catalyzed by Cationic Metal Phosphine Complexes

Abstract: The discovery of complementary methods for enantioselective transition-metal-catalyzed cyclization with silyloxyenynes has been accomplished using chiral phosphine ligands. Under palladium catalysis, 1,6-silyloxyenynes bearing a terminal alkyne led to the desired 5-membered ring with high enantioselectivities (up to 91% ee). As for reactions under cationic gold catalysis, 1,6- and 1,5-silyloxyenynes bearing an internal alkyne furnished the chiral cyclopentane derivatives with excellent enantiomeric excess (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 89 publications
1
55
0
Order By: Relevance
“…Av ariety of functionalities, including cyano (3), ether (7,8), ester (15,16), olefin (14), enolizable ketone( 5), amide (18), carbamate( 19), sulfonamide (20)a sw ella sf ree amine (9)a nd hydroxy( 10-13) groups are wellt olerated. Thes cope of the reaction also covers ar age of brominated heterocyclic partners (21-31), including nitrogen-containingh eterocycles (23-30)-moieties of particular importance for medicinal chemistry.F urthermore,i tw as shown that vinyl bromides are also compatible with the reactionc onditions,l eading to corresponding dienes (32-33)i ng ood yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Av ariety of functionalities, including cyano (3), ether (7,8), ester (15,16), olefin (14), enolizable ketone( 5), amide (18), carbamate( 19), sulfonamide (20)a sw ella sf ree amine (9)a nd hydroxy( 10-13) groups are wellt olerated. Thes cope of the reaction also covers ar age of brominated heterocyclic partners (21-31), including nitrogen-containingh eterocycles (23-30)-moieties of particular importance for medicinal chemistry.F urthermore,i tw as shown that vinyl bromides are also compatible with the reactionc onditions,l eading to corresponding dienes (32-33)i ng ood yields.…”
Section: Resultsmentioning
confidence: 99%
“…Pd(II) intermediate 50,f ormed via oxidative addition of aryl bromidet oP d(0) species 49,a ctivates alkyne through p-coordination, producing 51.T hent he base triggers 5-exo-dig cyclizationt of orm (E)-vinylpalladium intermediate 52,w hich undergoes reductive elimination, liberating product, regenerating active Pd(0) species 49 and thus closing the catalytic cycle.S uch ap athway is strongly supported by stereochemical outcome of the reactiona nd is consistent with previous reports. [16] Thep ostulated vinylpalladium intermediatem ight undergo protodepalladation instead of reductive elimination, leading to the formation of Conia-ene product 53,w hich could be considereda ni ntermediatei n the catalytic cycle.H owever, independently obtained 53 did not undergo the Heck reactionu nder the normal reactionc onditions.…”
Section: Resultsmentioning
confidence: 99%
“…4c). 27 In addition, this group reported gold- and palladium-catalyzed cyclizations of silyloxyenynes 28 and a palladium-catalyzed variant of the Conia-ene reaction 29 to access functionalized cyclopentenes containing quaternary stereocenters. Rhodium catalysis has also been applied to the cyclization of dienynes to construct bicyclic, spirocyclic, and fused products depending upon the nature of the substrate.…”
Section: Polyene Cyclizationsmentioning
confidence: 99%
“…Gold-catalyzed transformations employing mild reaction conditions appeared during the last twelve years [26,27,28]. Initially, coordination arrangements of chiral gold complexes avoided high enantiodiscriminations but, recently, it has been demonstrated that chiral bis-gold complexes type 24 ( Figure 4) are very efficient in asymmetric catalysis [56,57]. However, classical 1,3-dipolar cycloaddition of iminoesters and electrophilic olefins was not described using gold complexes.…”
Section: Gold-catalyzed 13-dc Of Azomethine Ylidesmentioning
confidence: 99%